Do factors in the psychosocial work environment mediate the effect of socioeconomic position on the risk of myocardial infarction? Study from the Copenhagen Centre for Prospective Population Studies. Issue 11 (11th October 2004) - Andersen, I; Burr, H; Kristensen, T S; Gamborg, M; Osler, M; Prescott, E; Diderichsen, F
Abstract : Aim: To investigate whether the effect of socioeconomic position on risk of myocardial infarction (MI) is mediated by differential exposure or differential susceptibility to psychosocial work environment. Methods: Data were used from three prospective population studies conducted in Copenhagen. A total of 16 214 employees, 44% women, aged 20–75 years, with initial examination between 1974 and 1992 were followed until 1996 for incident (hospital admission or death) MI. Register based information on job categories was used. Psychosocial job exposures were measured indirectly by means of a job exposure matrix based on the Danish Work Environment Cohort Study 1990. Results: During follow up, 731 subjects were diagnosed with an MI: 610 men and 121 women (35% fatal). The hazards by socioeconomic position showed a graded effect with a hazard ratio (HR) of 1.57 (95% CI 1.23 to 2.03) for unskilled workers compared to executive managers. Despite a strong and graded association in risk of MI related to decision authority and skill discretion, only skill discretion mediated the effect of socioeconomic position. The HR for unskilled workers was reduced to 1.47 (0.93 to 2.31) after adjustment for decision authority and other cardiovascular risk factors, and to 1.07 (0.72 to 1.60) after adjustment for skill discretion and cardiovascular risk factors. No sign of synergy was found. Conclusions: Decision authority and skill discretion were strongly related to socioeconomic position; and the effect on risk of MI was partially mediated by skill discretion. Improvements in psychosocial work environment, especially possibilities for skill discretion, might contribute to reducing the incidence of MI and social inequality in MI.